جهود المحدثين والمؤرخين في تدوين السيرة النبوية وكتابتها - العطيف، علي بن محمد بن حسن (جامعة الملك خالد, 2016)
جهود المحدثين والمؤرخين في تدوين السيرة النبوية وكتابتها. ظهر منهجان مبكران في تدوين السيرة: اتجاه المؤرخين واتجاه المحدثين، وإن كان التمايز بين هذين المنهجين لم يظهر بوضوح في المرحلة الأولى من الاهتمام بالسيرة، فقد كان أعلام المهتمين بالسيرة من كبار المحدثين مثل عروة بن الزبير والزهري، لكن سرعان ما تمايز كل منهج عن الآخر، مع الوضع في الاعتبار أن منهج المؤرخين التزم، بوجه عام، بالاستناد كما هو عند المحدثين، وإن كان هذا الالتزام عندهم تختلف درجته عما هي عليه عند المحدثين. وقد اتبعت منهج الاستقراء وتحليل النصوص المهمة في هذا الموضوع، وقد خرجت في هذا البحث بعدة نتائج من أهمها: أهمية متابعة البحوث والدراسات العلمية الجادة في مجمل القضايا والمسائل المتصلة بعلم السيرة النبوية. ورفض دعوى الاكتفاء بجهود السابقين والوقوف عندها وعدم الزيادة عليها، بل يجب التفنن والإبداع، والدقة البالغة في تمحيص وتحقيق وتخريج بعض القضايا الجزيئة في جوانب السيرة النبوية بطولها وعرضها. وأيضا، تميز العصر الحاضر بجملة كبيرة من الكتابات حول السيرة النبوية، تنوعت ملامحها من ناحية: الموضوع والفكر، وطريقة العرض، مما جعل موضوع السيرة النبوية من أكثر الموضوعات انتشارا وبيانا، في محيط المسلمين وغير المسلمين.
Two early approaches appeared in recording the biography of the Prophet (Sira): the approach of historians and that of Hadith scholars (traditionists), although the distinction between these two approaches did not appear clearly in the first stage of interest in the Sira. The most prominent scholars who took interest in the Sira were 'Urwa b. Alzubayr and Ibn Shihab al-Zuhri. Nevertheless, both approaches started to be quickly distinguished from each other, taking into an account that the approach of historians adhere – in general - to using isnad (chain of narrators) as used by scholars of hadith, although their commitment to that was varied and not at the same level as it was used by scholars of hadith. In this study, I have applied induction and analysis method for the most important texts of the subject. Some significant results reached in this study are: following up serious research and scientific studies in all issues related to the biography of the Prophet are necessary. The idea of sufficiency of early efforts in this filed and not to enhance or revise it should be refused, and it is important to do more creative and critical research in all aspects of Sira. The present era is distinguished by a large number of writings on the Prophet's biography, which varied in terms of subject matter, thought, and presentation, which made the subject of the Prophet's biography one of the most widespread topics in the Muslim and non-Muslim worlds
Keywords: السنة النبوية -- السيرة النبوية -- المحدثين -- المؤرخين